Analisis Pengaruh Kepemimpinan, Lingkungan Kerja dan Stres Kerja terhadap Kinerja Karyawan PDAM Tirta Raja OKU - Fredy Valentino; Munajat Munajat; Rini Efrianti (Jurnal Ekonomi, Manajemen, dan Bisnis, 2026)
This study aims to examine the extent to which leadership, work environment, and job stress influence employee performance at PDAM Tirta Raja OKU. The population in this study was 156 employees, while the sample used was 61 respondents determined through a specific sampling technique. The study used a quantitative approach with a questionnaire as the data collection tool. Furthermore, the data were analyzed using multiple linear regression methods to determine the influence of each variable individually and their combined influence. The analysis results show that leadership and the work environment have a positive and significant influence on improving employee performance. Conversely, work stress has been shown to have a negative but still significant influence on performance. Simultaneously, these three variables have a significant contribution to the performance of PDAM Tirta Raja OKU employees. The research findings indicate that leadership quality, work environment conditions, and employee stress levels are important factors that determine performance levels. Therefore, efforts to improve performance can be carried out through the implementation of effective leadership, the creation of a supportive work environment, and optimal work stress management.